2003
DOI: 10.1016/s0037-0738(03)00176-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-depth calcareous contourites in the latest Cretaceous of Caravaca (Subbetic Zone, SE Spain). Origin and palaeohydrological significance

Abstract: Deep marine carbonates of Late Campanian to Early Maastrichtian age that crop out in the Subbetic Zone near Caravaca (SE Spain) contain a thick succession of dm-scale levels of calcareous contourites, alternating with fine-grained pelagitesl hemipelagites. These contourites, characterised by an abundance and variety of traction structures, internal erosive surfaces and inverse and nOlmal grading at various scales, were interpreted as having been deposited under the influence of relatively deep ocean CUlTents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The high amount of planktonic biota in the cross-bedded bioclastic grainstones ( Fig. 5 c) suggests sediment shifting by bottom currents on the outer ramp ( Stow et al, 1996; Martín-Chivelet et al, 2003 ). Bioturbated mudstones with abundant planktonic foraminifers, sponge spicules and radiolarians characterise the distal outer ramp of the Oligocene–Miocene carbonate platforms in the central Apennines ( Brandano et al, 2012; Pomar et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high amount of planktonic biota in the cross-bedded bioclastic grainstones ( Fig. 5 c) suggests sediment shifting by bottom currents on the outer ramp ( Stow et al, 1996; Martín-Chivelet et al, 2003 ). Bioturbated mudstones with abundant planktonic foraminifers, sponge spicules and radiolarians characterise the distal outer ramp of the Oligocene–Miocene carbonate platforms in the central Apennines ( Brandano et al, 2012; Pomar et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of fragmentation and abrasion of the allochems is consistent with the action of strong bottom currents (Martín-Chivelet et al, 2003, 2008Longhitano et al, 2014;Rebesco et al, 2014;Lüdmann et al, 2018;Eberli and Betzler, 2019;Longhitano and Chiarella, 2020). The bioclastic fraction of the facies with abundant bryozoans, echinoids, molluscs, and red algae is a typical Miocene bryomol assemblage (Nelson, 1988).…”
Section: Composition and Texture Of The Sedimentmentioning
confidence: 57%
“…Mud floccule ripples created in flume experiments were produced under suspended sediment concentration of tens of mg/L (Schieber and Southard, 2009). Therefore, bottom-current reworked deposits show rare massive (by en masse deposition) or graded beds (Shanmugam et al, 1993a(Shanmugam et al, , 1993bShanmugam, 2017;Martín-Chivelet et al, 2003;, and common laminated and rippled facies, as found in the described facies associations. Although laminated and rippled facies are also common in turbidites, in our dataset they are not part of the typical Bouma sequence (Tc; Figs.…”
Section: Evidence Of Low Sediment Concentrationmentioning
confidence: 75%
“…For instance, both low-density turbidity flows (sensu Stow and Shanmugam, 1980) and bottom currents (Shanmugam et al, 1993a(Shanmugam et al, , 1993bShanmugam, 2006) record traction transport at the base of the flow. The associated deposits differ by the vertical arrangement of sedimentary structures: turbidites typically record traction structures from a waning flow, whereas bottom current deposits do not (Martín-Chivelet et al, 2003). Hyperpycnal flow deposits share an additional characteristic with bottom currents: inverse-to-normally graded beds due to waxing-to-waning flows that can be confused with the similar bi-gradational energy profile of contourites (Mulder, 2011).…”
Section: Presence Of Bottom Currents In the Vaca Muerta Formationmentioning
confidence: 99%
See 1 more Smart Citation